47. CLINICAL, SUBCLINICAL CHARACTERISTICS OF CHILDREN WITH PNEUMONIA CAUSED BY RESPIRATORY SYNCYTIAL VIRUS BACTERIAL CO-INFECTIONS (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the clinical, subclinical characteristics of children with pneumonia caused by respiratory syncytial virus, bacterial co-infection.Subjects and methods: A descriptive study was conducted on 283 children aged 1-24 months with respiratory syncytial virus pneumonia who were hospitalized at the Center for Pulmonology and Respiratory Care, Vietnam National Children’s Hospital, from August 2022 to November 2023.Results: The rate of bacterial co-infection in children with respiratory syncytial virus pneumonia was 57.2%, with a higher prevalence in the 6-11 months age group (p < 0.05). Children with bacterial co-infection were 3.66 times more likely to have fever compared to those without co-infection, with fever rates of 74.7% and 44.6%, respectively (p < 0.05). The bacterial co-infection group also showed a significantly higher prevalence of both dry rales and moist rales (p < 0.05). In terms of subclinical findings, white blood cell count, neutrophil count, and CRP levels were significantly elevated in the co-infection group (p < 0.01). Notably, the risk of elevated CRP levels (≥ 6 mg/dl) was 4.3 folds higher in the bacterial co-infection group compared to the non-co-infection group (95%CI: 2.6-7.2; p < 0.0001).Conclusion: Bacterial co-infection is common in children with respiratory syncytial virus pneumonia and is associated with more severe clinical manifestations, including fever, dry rales and moist rales, as well as elevated white blood cell counts and CRP levels
Keywords: Pneumonia; RSV; CRP; children